Parallelisable variants of Camellia and SMS4 block cipher: p-Camellia and p-SMS4. (1st January 2013) - Yap, Huihui; Khoo, Khoongming; Poschmann, Axel
We propose two parallelisable variants of Camellia and SMS4 block ciphers based on the n -cell GF-NLFSR. The n -cell generalised Feistel-non-linear feedback shift register (GF-NLFSR) structure (Choy et al., 2009a) is a generalised unbalanced Feistel network that can be considered as a generalisation of the outer function FO of the KASUMI block cipher. An advantage of this cipher over other n -cell generalised Feistel networks, e.g., SMS4 (Diffe and Ledin, 2008) and Camellia (Aokiet al., 2001), is that it is parallelisable for up to n rounds. In hardware implementations, the benefits translate to speeding up encryption by up to n times while consuming similar area and significantly less power. At the same time, n -cell GF-NLFSR structures offer similar proofs of security against differential cryptanalysis as conventional n -cell Feistel structures. In this paper, we prove security against differential, linear and boomerang attacks. We also show that the selected number of rounds are conservative enough to provide high security margin against other known attacks such as integral, impossible differential, higher order differential, interpolation, slide, XSL and related-key differential attacks.